Factors Influencing Employees to Stay in an Organisation - Adi, Nazir; Ma’arof, Amirah Nuraisyah; Mohd Angsor, Mohd Asmadi (Research in Management of Technology and Business, 2020)
Manufacturing industry is one of the main sectors that contribute to the Gross Domestic Product (GDP) in Malaysia. However, at the same time, the manufacturing industry also faced problems in retaining their current employees. Therefore, the purpose of this study is to examine the relationship between compensation, career opportunity, training and development and performance appraisal toward intention to stay among employees of manufacturing companies in Sri Gading Industrial Area, Batu Pahat, Johor. Structured questionnaires were distributed to 250 employees based on random sampling method. Statistical Package for Social Sciences (SPSS) version 22 was used to analyse the data. The results support all of the hypotheses tested. The findings show that all independent variables are significantly correlated with intention to stay; compensation (r=0.894, p<0.01), career opportunity (r=0.692, p<0.01), training and development (r=0.692, p<0.01), and performance appraisal (r=0.944, p<0.01). Based on the findings, various strategies were suggested which have wider managerial and policy implications for the management of intention to stay in similar settings